2007
DOI: 10.1189/jlb.0507272
|View full text |Cite
|
Sign up to set email alerts
|

A SELDI-TOF MS study of the genetic and post-translational molecular heterogeneity of eosinophil cationic protein

Abstract: Eosinophil cationic protein (ECP), a secretory protein of the eosinophil granulocyte, is a basic and highly heterogeneous protein. This heterogeneity is dependent on polymorphisms in the ECP gene and post-translational modifications, and it affects the functional properties of the protein in terms of cytotoxicity. The aim of this study was to further investigate the molecular heterogeneity, hence, an affinity capture assay based on an antigen-antibody interaction with the surface-enhanced laser desorption/ioni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
1
8

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(49 citation statements)
references
References 26 publications
1
39
1
8
Order By: Relevance
“…In addition to chronic inflammatory disorders, including asthma and COPD, a number of studies have addressed the involvement of eosinophils and their granule proteins in host resistance to parasites, their antimicrobial activities toward bacterial, viral and protozoan pathogens, their function as mediators of hypersensitivity and their interactions with the coagulation system (22,38). Case reports have stated that eosinophilia in patients may be accompanied by thromboembolisms (40)(41)(42).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to chronic inflammatory disorders, including asthma and COPD, a number of studies have addressed the involvement of eosinophils and their granule proteins in host resistance to parasites, their antimicrobial activities toward bacterial, viral and protozoan pathogens, their function as mediators of hypersensitivity and their interactions with the coagulation system (22,38). Case reports have stated that eosinophilia in patients may be accompanied by thromboembolisms (40)(41)(42).…”
Section: Discussionmentioning
confidence: 99%
“…ECP has various biological activities, including antibacterial, antiviral, antiparasitic and neurotoxic functions, and it contributes to the regulation of fibroblast activity (21). ECP also induces airway mucus secretion and interacts with the coagulation and complement systems (22,23). Fiorini et al (24) concluded that serum ECP levels increased during AECOPD.…”
Section: Introductionmentioning
confidence: 99%
“…Samples were analyzed on PS20 ProteinChip arrays in a PBS-IIC system or PCS 4000 Enterprise system (Bio-Rad Laboratories) as described previously (13). A monoclonal anti-ECP Ab, clone 614 provided by Diagnostics Development, was used.…”
Section: Seldi-tof Ms Affinity Capture Assaymentioning
confidence: 99%
“…Supernatants and cell extracts were incubated with or without 3 U of Nglycosidase F (Roche Diagnostics) at 37°C overnight as has been described before (13).…”
Section: Enzymatic Deglycosylation Of Ecpmentioning
confidence: 99%
See 1 more Smart Citation